2021
DOI: 10.1186/s13578-021-00639-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions of autophagy in vascular calcification

Abstract: Background Vascular calcification is a closely linked to cardiovascular diseases, such as atherosclerosis, chronic kidney disease, diabetes, hypertension and aging. The extent of vascular calcification is closely correlate with adverse clinical events and cardiovascular all-cause mortality. The role of autophagy in vascular calcification is complex with many mechanistic unknowns. Methods In this review, we analyze the current known mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 106 publications
1
27
0
Order By: Relevance
“…In atherosclerotic plaque, there is an increase expression of autophagy related proteins [ 21 ]. In order to explore the possible mechanisms of how TXNIP mediated galectin-3-induced VSMCs osteogenic differentiation, we focus on the autophagy process.…”
Section: Resultsmentioning
confidence: 99%
“…In atherosclerotic plaque, there is an increase expression of autophagy related proteins [ 21 ]. In order to explore the possible mechanisms of how TXNIP mediated galectin-3-induced VSMCs osteogenic differentiation, we focus on the autophagy process.…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent study, inhibition of the PI3K-Akt-mTOR pathway promotes osteogenic/dentine differentiation in SCAPs in vitro and in vivo ( Tanaka et al, 2018 ). Recent studies have shown that osteoblasts derived from vascular smooth muscle cells (VSMCs) and MSCs are modulated by autophagy to promote the transformation of calcification signals in vascular structures ( Shanahan, 2013 ; Lee et al, 2014 ; Caffarelli et al, 2017 ; Zhou et al, 2021 ). With the involvement of autophagic proteins, AMPK activation powerfully links Akt/mTOR-associated autophagy to the osteogenic differentiation of MSCs ( Zhou et al, 2021 ).…”
Section: Effects Of Mammalian Target Of Rapamycin On Mesenchymal Stem...mentioning
confidence: 99%
“…Recent studies have shown that osteoblasts derived from vascular smooth muscle cells (VSMCs) and MSCs are modulated by autophagy to promote the transformation of calcification signals in vascular structures ( Shanahan, 2013 ; Lee et al, 2014 ; Caffarelli et al, 2017 ; Zhou et al, 2021 ). With the involvement of autophagic proteins, AMPK activation powerfully links Akt/mTOR-associated autophagy to the osteogenic differentiation of MSCs ( Zhou et al, 2021 ). MiR-100-5p and miR-143-3p are involved in regulating the mTOR signaling pathway and promoting osteogenesis ( Cen et al, 2021 ).…”
Section: Effects Of Mammalian Target Of Rapamycin On Mesenchymal Stem...mentioning
confidence: 99%
“…Other novel drivers for VC are autophagy and mitochondrial dysfunction. Autophagy has multiple functions in VC, as reviewed elsewhere ( 9 ). It affects VC by interfering with osteogenic differentiation of VSMCs, inhibition of apoptosis, and regulation of MV release.…”
Section: A Brief Overview and Update In The Mechanism Of Vascular Cal...mentioning
confidence: 99%